2016
DOI: 10.1016/j.hpb.2016.01.173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of percutaneous portal vein embolization (pve) prior to major liver resection and alpps (associating liver partition and portal vein ligation for staged hepatectomy), single center experience

Abstract: Recurrence was greater with T3/4 disease compared to T1/2 disease (70% versus 60%) (p = 0.01). T1/2 disease in the <75 group was associated with fewer recurrences than <75 T3/4 disease group (p 0.001). Recurrence rates were comparable with T1/T2 disease and T3/T4 disease in the >75 years group (p = 0.190). There was no improvement in DFS with and without AC following hepatectomy in the >75 group (p = 0.161). However there was improved DFS between the <75 groups with AC and without AC (p 0.001). OS in the>75 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although the excluded liver has no portal flow, and is supplied by arterial vessels only, it acts as an auxiliary liver contributing to overall liver function until the contralateral lobe has grown sufficiently to support physiological function similar to that of a normal liver (1-3). There is growing evidence to support greater hypertrophy of the future liver remnant in ALPPS compared to PVE (10)(11)(12)(13)(14). Thus, as both stages of ALPPS may be achieved within 2 weeks, compared to 4-8 weeks in PVE, the advantage of ALPPS in patients with pre-existing liver disease and poor liver function is clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the excluded liver has no portal flow, and is supplied by arterial vessels only, it acts as an auxiliary liver contributing to overall liver function until the contralateral lobe has grown sufficiently to support physiological function similar to that of a normal liver (1-3). There is growing evidence to support greater hypertrophy of the future liver remnant in ALPPS compared to PVE (10)(11)(12)(13)(14). Thus, as both stages of ALPPS may be achieved within 2 weeks, compared to 4-8 weeks in PVE, the advantage of ALPPS in patients with pre-existing liver disease and poor liver function is clear.…”
Section: Discussionmentioning
confidence: 99%
“…Krishnamurthy et al reported 1-stage robotic ALPPS in India in 2018 (9). Evidence is emerging for the advantage of APPPS over portal vein embolization (PVE) in achieving greater hypertrophy of the future liver remnant sooner (10)(11)(12)(13)(14). This is an important factor in patients who already have impaired liver function.…”
Section: Introductionmentioning
confidence: 99%